Evaluasi Sifat Fisik, Kimia dan Mikrobiologi pada Susu Sapi Segar yang Didapat dari Beberapa Kelompok Ternak di KSU Mitra Jaya Mandiri Ciwidey, Kabupaten Bandung - Septiani, Silvia; Christi, Rd. Febrianto; Pratama, Andry (Jurnal Teknologi Hasil Peternakan, 2023)
Milk constituent components and milking hygiene affect the quality of fresh cow's milk. This study aims to determine the physical, chemical and microbiological properties of fresh cow's milk obtained from KSU Mitra Jaya Mandiri covering Ciwidey District, Pasirjambu District and Rancabali District, Bandung Regency, West Java. To determine the quality of fresh milk, it must go through tests such as alcohol tests, specific gravity, protein content, fat content, non-fat dry matter content, pH value and Total Plate Count in fresh cow's milk. The milk sample used in this study was cow's milk in the 2nd and 3rd lactation periods with a total sample of 26 for each lactation, 13 samples of fresh cow's milk. The research method used is a quantitative descriptive analysis by calculating the average, minimum, and maximum values, standard deviation, and coefficient of variation. The results showed that the average specific gravity was 1,029, the average protein content was 3,33%, the average fat content was 3,24%, the average BKTL was 9,15%, the average pH was 6,67, the average Total Plate Count was 18,4x105   CFU/mL, so Fresh cow's milk obtained from KSU Mitra Jaya Mandiri meets the criteria of the Indonesian National Standard (2011).